2019
DOI: 10.1159/000506229
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in Bone Geometry in Growth Hormone-Deficient Prepubertal Boys Revealed by High-Resolution Peripheral Quantitative Computed Tomography

Abstract: <b><i>Introduction:</i></b> Although growth hormone (GH) is essential for attainment of peak bone mass, bone health in prepubertal children with GH deficiency is not routinely evaluated. The objective of this study was to evaluate bone microarchitecture in GH-deficient (GHD) boys using high-resolution peripheral quantitative computed tomography (HR-pQCT). <b><i>Methods:</i></b> Fifteen control and fifteen GHD, GH naïve pre-pubertal boys were recruited for a case-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Studies have suggested a possible interaction between 25-hydroxyvitamin D and IGF-1 during prepubertal bone mineral accrual [2,3]. The key "bone trophic hormones", growth hormones (GH) and IGF-1, are essential for achieving peak bone mass [4,5]. GH acts directly on bone cells and stimulates IGF-1 to increase bone formation through the enhancement of osteoblasts proliferation, differentiation, and activity [4].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested a possible interaction between 25-hydroxyvitamin D and IGF-1 during prepubertal bone mineral accrual [2,3]. The key "bone trophic hormones", growth hormones (GH) and IGF-1, are essential for achieving peak bone mass [4,5]. GH acts directly on bone cells and stimulates IGF-1 to increase bone formation through the enhancement of osteoblasts proliferation, differentiation, and activity [4].…”
Section: Introductionmentioning
confidence: 99%